Serum thymus and activation-regulated chemokinelevels in children with atopic dermatitis - Tamila Sorokman; Snizhana Sokolnyk; Iryna Sokolnyk; Olena Makarova; Pavlo Moldovan (Amaltea Medical Publishing House, 2019)
Introduction. It is known that atopic dermatitis (AD) is characterized by infiltration of Th2 cells into affected skin. Infiltration of inflammatory cells in the tissue is mediated by specific chemokines. An important chemokine is Thymus and Activation-Regulated Chemokine (TARC). The purpose of the study is to investigate TARC levels in blood serum of children of different ages with different AD severity degrees. Methods. The scrutiny of immune status was conducted in 168 children with AD aged from 1 to 18 years. The inclusion criteria in the study were: age of patients from 1 to 18 years; residence in Chernivtsi region; confirmed AD. The severity of AD was set by the SCORAD Index. Serum IgE and TARC levels were determined. Results. Often, AD has occurred in young children, particularly from 2 to 6 years of age. The most prevalent in children with AD is food sensibilisation, which is found in 89.9% of cases. With age, the level of allergenic IgE in the blood of patients with AD and sensibilisation increased. The average indicator in the group of children with AD was 1322.8 ± 114.6 pg / ml, while in the group of healthy children - 399.8 ± 56.4 pg / ml. TARC levels decreased gradually with the age of children and correlated with activity and severity of AD (r = 0.58 and 0.77, accordingly, p <0.001). The highest TARC levels are registered in patients with severe AD. Conclusions. Biomarkers, such as TARC, can be used in pediatric practice to accurately assess the grade of invisible subclinical disorders and the severity of AD.